Robust fusion for skin lesion segmentation of dermoscopic images - Guo, Qingqing; Fang, Xianyong; Wang, Linbo; Zhang, Enming; Liu, Zhengyi (Frontiers in Bioengineering and Biotechnology, 2023)
Robust skin lesion segmentation of dermoscopic images is still very difficult. Recent methods often take the combinations of CNN and Transformer for feature abstraction and multi-scale features for further classification. Both types of combination in general rely on some forms of feature fusion. This paper considers these fusions from two novel points of view. For abstraction, Transformer is viewed as the affinity exploration of different patch tokens and can be applied to attend CNN features in multiple scales. Consequently a new fusion module, the Attention based Transformer-And-CNN fusion module (ATAC), is proposed. ATAC augments the CNN features with more global contexts. For further classification, adaptively combining the information from multiple scales according to their contributions to object recognition is expected. Accordingly, a new fusion module, the GAting based Multi-Scale fusion module (GAMS), is also introduced, which adaptively weights the information from multiple scales by the light-weighted gating mechanism. Combining ATAC and GAMS leads to a new encoder-decoder based framework. In this method, ATAC acts as encoder block to progressively abstract strong CNN features with rich global contexts attended by long-range relations, while GAMS works an enhancement of decoder to generate the discriminative features through adaptive fusion of multi-scale ones. This framework is especially good at lesions of varying sizes and shapes and of low contrasts and its performances are demonstrated with extensive experiments on public skin lesion segmentation datasets.